Factors Influencing the Stock Price of Banking Companies in the Indonesia Stock Exchange - Muria Kartika Perdana; Constance Henryette Adriana (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2018)
The banking sector is the industry most regulated by the government has given the importance of this sector in the country's economy as a bridge for financing the real sector. Stocks in the banking industry are one of the stocks that are highly sought after by investors. Banks that have good health will attract many investors. The purpose of this study is to prove the influence of the bank's health level – risk profile and good corporate governance – on stock price in the banking sector companies on the IDX. The data used in this study are secondary data in the form of financial statements of banking companies. The independent variables in this study are risk profile and GCG, which consist of Non Performing Loans (NPL), Interest Rate Risk (IRR), Loan to Deposit Ratio (LDR), Managerial Ownership, Institutional Ownership, Independent Commissioner, Size of Board of Directors, Committee Audit and dependent variable Share Price. The sampling method in this study was purposive sampling with a sample of 7 banking companies registered on the Indonesia Stock Exchange. The stock price is the closing price on Yahoo Finance. The data analysis technique used is a parametric statistical test – multiple linear regression analysis and classical assumption test, including normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. Test of hypothesis used the R Square test, partial t-test, and F test. The results of the study prove that the Non-Performing Loan (NPL), Independent Commissioner, and Audit Committee variables have no influence on the Stock Price. However, the Interest Rate Risk (IRR), Loan to Deposit Ratio (LDR), Managerial Ownership, Institutional Ownership, and the Size of the Board of Directors have an effect on Stock price.